A Ramsey theorem for partial orders with linear extensions. (February 2017) - Solecki, Sławomir; Zhao, Min
Abstract: We prove a Ramsey theorem for finite sets equipped with a partial order and a fixed number of linear orders extending the partial order. This is a common generalization of two recent Ramsey theorems due to Sokić. As a bonus, our proof gives new arguments for these two results.